Italian Style. La cifra del realismo politico - Portinaro, Pier Paolo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
It is surely true that what is currently called “Italian Theory” is rooted in a tradition of thought that has always paid attention to the intertwinement between the political and the theoretical dimension of philosophy. Nevertheless, it is also true that the so called “Italian Theory” – and the emphasis put abroad on it, in a sort of mimicry of the “French Theory” – overshadows important authors and strands of thought which represent much better what can be considered as unique and peculiar as regards the way the reflection on the political dimension took place within the Italian philosophical tradition. The article offers an overview of a specific strand within the Italian political theory that, moving from Gaetano Mosca’s and Vilfredo Pareto’s élite theory, encompasses authors like Salvemini, Gramsci, Bobbio, Sartori and goes as far as to include Pizzorno’s critical reflection on democratic representation.